(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article explores the role and potential of digital marketing strategies in shaping and enhancing the competitiveness of an innovative educational ecosystem at a modern university. In the context of digitalization and increasing competition in the global education market, universities are forced to transform from traditional educational institutions into open, networked ecosystems. The author argues that digital marketing is evolving from a promotion tool to a system-forming element that integrates all stakeholders (enrollees, students, graduates, academic staff, and industry partners), generates innovation, and creates a unique value proposition. Based on the analysis of modern concepts of educational ecosystems and digital marketing, a comprehensive model for integrating marketing strategies into the ecosystem architecture has been developed. The model includes a target, content, technological, and result-oriented blocks focused on personalizing the educational experience, building long-term relationships, and strengthening the university’s research and innovation potential. The theoretical significance of the work lies in the systematization of approaches to marketing educational ecosystems, while the practical significance lies in the proposal of specific tools and metrics for evaluating the effectiveness of digital marketing activities in the context of the university’s strategic development.